Effects of genistein on aggregation and cytosolic free calcium in pig platelets - Liu Wen; Song Zhi-Juan; Liang Nian-Ci (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of genistein on aggregation and cytosolic free calcium concentration in platelets. METHODS: Using turbidimetry to analyse aggregation and using Fura-2 fluorescence technique to determine Ca2+ level. RESULTS: Genistein strongly inhibited the pig platelet aggregation induced by thrombin (250 U.L-1). When genistein concentrations were 5 and 20 mumol.L-1, the inhibition rates on the aggregation were 52% and 73%, respectively. Genistein inhibited the rise of cytosolic free calcium concentration in platelets stimulated by thrombin (500 U.L-1) in the presence of extracellular Ca2+ 1 mmol.L-1. When genistein concentrations were 10, 20, 40, and 80 mumol.L-1, the inhibition rates were 24%, 40%, 63%, and 65%, respectively, but no effect on thrombin-induced internal Ca2+ release from dense tubular system. CONCLUSION: Genistein is a potential anti-platelet agent, mainly due to an inhibition of Ca2+ influx.